Primary bliary crrhosis in pregnancy - Olga Adamczyk-Gruszka; Izabela Lewandowska-Andruszuk; Marzena Wrześniewska; Jakub Gruszka; Karolina Komar-Gruszka (Journal of Education, Health and Sport, 2018)
Introduction Primary biliary cirrhosis (PBC) is a chronic hepatic condition presumably of immune etiology. In genetically predisposed patients, progressing immunization of the liver is stimulated by environmental or infectious agents. As a result of ill-targeted immune response antimitochondrial autoantibodies M2 (AMA-M2) are produced. They slowly damage fine intrahepatic biliary ducts with typical inflammatory response and subsequent cholestasis, often progressing to hepatic cirrhosis and liver failure, and if it has reached 4 stage, primary hepatic cancer. PBC is most frequently diagnosed in women after the age of 30. It is 13 times more frequent in females than in males. Currently, PBC is often diagnosed at the asymptomatic stage or when nonspecific symptoms have developed, i.e. fatigue or pruritus. Biochemical tests present elevated cholestatic markers, and immune tests detect elevated autoimmune antibodies AMA and IgM. In advanced cases of hepatic cirrhosis, liver transplant is considered as a final treatment. Case study